Costa Rican gut fungi (Trichomycetes) infecting lotic insect larvae - Lichtwardt, Robert W (Universidad de Costa Rica, 1997)
Trichomycetes infecting freshwater Ephemeroptera and Díptera (Siínuliidae, Chironomidae) in various life zones oC Cósta Rica were studied. Insect populations in 36 streams were sampled, a few repeatedly, at four different . perlods of time over seven years. Eleven new species of Harpellales are reported, plus six species known to occur also in n ontropical parts oí the world. Included are new species of Harpella and Pennella, a new monotypic genus (Graminelloides), and four new species of the previously monotypic genera Spartiella and Genistellospora. Seven new Smittiúm species, including three that are not named at this time, were cultured axenically. A new Amoebidium (Amoebidiales) was found in a stream polluted with organic matter. In the same polluted stream more species of dipteran larvae and a greater number of gut fungi were present than in stretclies of unpolluted water upstream. The overall diversity of Harpellales and their aquatic insect hosts in most Costa Rican streams appeared to be lower than what the author has found in many lotic habitats in more northem and southem regions of the world, and thus this order of fungi may be an exception to the 'latitudinal species diversity gradient' concept as it applies to many other tropical organisms. A key to all 23 Tric homycetes now k n o w n to be present in Costa R i c a is provided